Desempenho operacional de semeadora-adubadora em diferentes manejos da cobertura e da velocidade - Furlani, Carlos E. A. [UNESP]; Pavan Jr., Álvaro [UNESP]; Lopes, Afonso [UNESP]; Silva, Rouverson P. [UNESP]; Grotta, Danilo C.C. [UNESP]; Cortez, Jorge W. [UNESP] (FapUNIFESP (SciELO), 2007)
The present work aimed to evaluate the seeder performance in the direct sowing system. The studied factors were three cover crop managements, chosen according to the size of the vegetation fragment, such as straw (straw totally triturated), weeder (straw partially chopped) and knife-rolls (straw practically entire), combined with three speeds of the seeder, being 4.0; 5.0 and 6.0 km h -1. The experimental outlining was carried out in casual blocks in factorial scheme 3 x 3, with nine treatments and eight repetitions, totalizing 72 observations. In the course of the experiment the following variants were evaluated: effective field capacity, force and power in the bar, hourly and area consumption of fuel and tractor's pulleys sliding. The data reached were tabulated and submitted to factorial variant analysis. When the value of the F test was significant at 0.05 of probability, the Tukey test was carried out to compare the averages. The three managements in the vegetal covering culture did not influence the seeder performance. The force decreased with the increasing of the forward speed, the opposite happened to the operational field capacity and the power in the bar. The hourly consumption of fuel increased with the speed, while the operational decreased.
Operational performance of seeder in different forward speed and winter cover crop management
Keywords: Direct sowing; Force; Fuel consumption